Adoption model of m-government services - Bílková, Renáta; Králová, Anna (IEEE (Institute of Electrical and Electronics Engineers), 2017)
E-government is an important tool for public sector transformation. The number of e-services available on government websites continues to grow by leaps and bounds. The usage of mobile technologies in the public administration not only provides an alternative communication and services channel for citizens, but also allows to go further. M-government is emerging as the next big wave for ICT use in the public sector. The aim of this article is to find out what are the factors that affect user acceptance of mobile e-government services or how can we motivate the citizens to utilize services. This paper applies the technology acceptance model to explore users' requirements for the adoption and usage of e-government services.
Aplikace TAM modelu v oblasti služeb m-governmentu
Keywords: e-government; m-government; technology acceptance model (TAM); e-government; m-government; technology acceptance model (TAM)